2022-RA-966-ESGO Tolerance of intraperitoneal (IP) nivolumab after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in patients (pts) with relapse advanced ovarian carcinoma: a phase I study with expansion cohort (ICONIC). (20th October 2022) - Corbaux, Pauline; You, Benoit; Bakrin, Naoual; Glehen, Olivier; Freyer, Gilles
Abstract : Introduction/Background: Cytoreductive surgery and HIPEC combination with intraperitoneal immunotherapy may have a synergic effect, through an increase of tumor-antigen expression and of mutational load. We aimed to determine the safety of IP nivolumab after CRS and HIPEC in pts with relapsed ovarian carcinoma (NCT03959761 ). Methodology: Patients were treated according to three dose-levels of IP nivolumab following a 3+3 design (0.5 mg/kg, 1 mg/kg, and 3 mg/kg), starting 5 to 7 days after DS and HIPEC and repeated every 2 weeks for 4 infusions. The primary objective was to establish the maximum tolerated dose (MTD) of IP nivolumab based on dose limiting toxicity (DLT) occurrence during the 28 days after the first IP nivolumab infusion. Secondary objectives were to assess disease progression, tolerance of DS, HIPEC and post procedure intravenous chemotherapy. Results: A total of 9/10 pts enrolled into the dose escalation were evaluable for DLT (1 peritoneal catheter fall-out after the 2nd infusion). No DLTs have been observed at either dose level according to an independent data safety monitoring board (DSMB), and 7 pts were included into an expansion cohort. In total, six pts (35.3%) did not complete all planned cycles. No deaths due to treatment occurred. Nine pts (52.9%) experienced severe adverse events (SAEs), 4 related to peritoneal catheter implant. SAEs were transaminases elevation (6 pts, grade 3–4, related to DS), hemodynamic shock (1 pt, related to DS), hypokalemia (1 pt, related to DS and HIPEC), portal vein thrombosis (1 pt, related to DS). There were no SAEs related to IP nivolumab. With a median follow-up of 10.1 months (95%CI 8.2-NA), median progression-free-survival was 7.4 months (95%CI 6.0-NA). Conclusion: IP nivolumab was feasible and well tolerated, supporting the pursuit of studies investigating this pioneering approach with other immunotherapy combination for example.